Clinical predictors of poor outcome of bacterial meningitis in infants less than 90 days: a systematic review - Liu, Ying; Feng, Yu; Guo, YanPing; Chen, JingJing; Liu, Chang; Liang, JiaBi (Frontiers in Pediatrics, 2024)
Background: bacterial meningitis (BM) is more common in infants than at any other time in life and remains a devastating disease with considerable risk of death and morbidity. This article aims to gather the currently available evidence to perform a systematic review of clinical factors that may predict or be associated with BM death and / or sequelae in infants < 90 days of age. Methods: The Medline/PubMed, Cochrane Library and Embase databases were systematically searched for prognostic studies that described risk factors for mortality and sequelae in infants aged <90d with BM. The databases were searched from the beginning of the database to December 31st, 2022.The quality of cohort studies was assessed by the Newcastle-Ottawa Scale (NOS). The quality of cross-section studies was assessed by the Agency for Healthcare Research and Quality (AHRQ). A systematic review was undertaken to ascertain the prognostic factors proven to be noteworthy.Results: Of the 1431 studies retrieved, 20 were eligible for the final analysis including 11 cohort and 9 cross-sectional studies were identified. Four risk factors predicting poor outcome were mentioned mostly in those studies, including prematurity or low birth weight (LBW), seizures, coma, and elevated CSF protein. But only preterm, coma and elevated CSF protein were identified by multivariate analyses in more than one study. Conclusions: This study demonstrates several potential predictive factors to the poor outcomes of BM in infant. But with large heterogeneity, these predictors should be evaluated by further well-designed prospective studies.